Language Style used by Victoria in the Movie Entitled “The Young Victoria” - Vitariani, I Gusti Agung (Udayana Journal of Social Sciences and Humanities; Vol 6 No 1 (2022): UJoSSH, February 2022, 2022)
This study is aimed at identifying the types of language style and analyzing the social factor influence the use of language style in the movie. The data of this study were taken from a movie entitled The Young Victoria and it was released on March 6, 2009. The documenation method through note taking technique was used to collect data. In analyzing the data,  descriptive qualitatively using theory proposed by Joos (1967) to identify the types of language style and the theory context of situation from Holmes (2013) was applied to analyze the social fators influence the choice of language style. This study presented five examples of language style and it found that there were five kinds of language style, including frozen style, formal style, consultative style, casual style, and intimate style used by Victoria as the main character in the movie. Moreover, the usage of language style influenced by social factors, such as participants, setting, topic, and function.